The Ronne Ice Shelf survived the last interglacial - Eric W. Wolff; Robert Mulvaney; Mackenzie M. Grieman; Helene M. Hoffmann; Jack Humby; Christoph Nehrbass-Ahles; Rachael H. Rhodes; Isobel F. Rowell; Louise C. Sime; Hubertus Fischer; Thomas F. Stocker; Amaelle Landais; et al. (Nature, 2025)
Abstract The fate of the West Antarctic Ice Sheet (WAIS)1 is the largest cause of uncertainty in long-term sea-level projections. In the last interglacial (LIG) around 125,000 years ago, data suggest that sea level was several metres higher than today2–4, and required a significant contribution from Antarctic ice loss, with WAIS usually implicated. Antarctica and the Southern Ocean were warmer than today5–8, by amounts comparable to those expected by 2100 under moderate to high future warming scenarios. However, direct evidence about the size of WAIS in the LIG is sparse. Here we use sea salt data from an ice core from Skytrain Ice Rise, adjacent to WAIS, to show that, during most of the LIG, the Ronne Ice Shelf was still in place, and close to its current extent. Water isotope data are consistent with a retreat of WAIS9, but seem inconsistent with more dramatic model realizations10 in which both WAIS and the large Antarctic ice shelves were lost. This new constraint calls for a reappraisal of other elements of the LIG sea-level budget. It also weakens the observational basis that motivated model simulations projecting the highest end of projections for future rates of sea-level rise to 2300 and beyond.